Contested Legacies Critical Perspectives on Postwar Modern Housing - MIGOTTO, ANDREA; Tattara, Martino (Leuven University Press, 2023)
New insights on the controversial and often-overlooked postwar large-scale housing estates. In the light of the current housing and environmental crisis and increasing social inequalities, there is a growing sense of urgency for architecture as a discipline to engage with the transformation in housing evident in the postwar period. Rather than conceiving this task as a technical matter, this book proposes to reassess the conditions and legacy of this large and ubiquitous housing stock. By foregrounding the mismatch between constructed cultural, social and ideological narratives and the everyday realities of residents, the contributors rediscover some of the tropes of modern housing, such as the impact of technological innovations or the often overlooked character of open spaces, and unveil the intellectual and practical tools that paved the way for this large-scale construction. Contested Legacies advances a new notion of heritage which, rather than seeking to preserve the past, sets outs to actively transform what exists to meet current societal needs. It offers an 'atlas' of exemplary cases, each illustrating a defining yet often neglected aspect of modern postwar housing, from which present engagement and active reflection can grow, making the book an appealing read for both scholars and housing practitioners worldwide. Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).